Limpets of the genus Cellana (Patellogastropoda) from Pakistan, North Arabian Sea: species identification based on DNA sequencing. (3rd July 2016) - Zafar, Fatima Hayat Shaheen; Ayub, Zarrien; Begum, Samar; Siddiqui, Ghazala; Roberts, David
Abstract: The true limpets are found in the intertidal zone of the rocky shores of Pakistan, North Arabian Sea. Partial sequence of the mitochondrial cytochrome oxidase I was used to estimate the degree of genetic differentiation among the morphological forms of Cellana, which were considered as three separate species earlier in Pakistan. The study revealed that the three morphs of Cellana on COI sequence generated a single haplotype and matched with the COI sequence of Cellana karachiensis . This point out the phenotypic plasticity between the proposed species.